Ion-Exchange Microemulsions for Eliminating Dilute Interferences in Potentiometric Determinations - Sutasinee Apichai (2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim We report here for the first time on the use of functional microemulsions in potentiometric assays to remove dilute interferences from solution when measuring high concentrations of analyte. The microemulsions are similarly formulated to the ion-selective membrane used in the measurement and act as sacrificial material. They are here stabilized by the triblock copolymer pluronic F-127 and contain the chloride salt of the tridodecylmethylammonium cation, which also serves as anion-exchanger in the membrane electrode. Both membrane and microemulsion are preconditioned with chloride. If an anionic interference is present at moderate concentration, the rapid equilibration with the functionalized microemulsion results in a quantitative removal. The principle is explored with salicylate as common interference in the detection of chloride in physiological samples. The data agree well to an equilibrium ion-exchange model for the microemulsion. Salicylate levels up to millimolar can be effectively removed. Unfortunately, quaternary ammonium salt from the microemulsion is found to contaminate the ion-selective membrane phase. Indeed, a cation-exchanging valinomycin membrane in contact with concentrated anion-exchanging microemulsions shows a large potential increase. This indicates that the membrane changes from cation to anion permselectivity. This contamination of the membrane by the microemulsion phase must be overcome for a practical application of the approach.